Peran Dinas Sosial dalam Penanggulangan Angka Kemiskinan di Kabupaten Pasaman Barat - Weni Puji Hastuti; Jufrizel; Siti Nur Fiza (Yayasan Almanar Pujud, 2025)
Poverty remains one of the major social issues that continues to receive significant attention from the government, including in West Pasaman Regency, where poverty rates have fluctuated over the years. The Social Service Office, as the implementing agency for social affairs, plays a crucial role in poverty alleviation through various programs, policies, and social services. This study aims to analyze the role of the Social Service Office in reducing poverty rates and to identify the inhibiting factors encountered in its implementation. This research employs a qualitative method with data collected through observations, interviews, and documentation. The findings indicate that the Social Service Office has carried out the four main governmental roles proposed by Arif (2012), namely as a regulator, dynamist, facilitator, and catalyst. The institution implements several social assistance programs such as PKH, BPNT, and PBI-JK, conducts community empowerment initiatives, updates the Integrated Social Welfare Data (DTKS), and provides various welfare services. However, several obstacles are still encountered, including limited budget allocation, inaccurate beneficiary data, insufficient human resources, and challenges in cross-sector coordination. Therefore, optimizing the role of the Social Service Office is essential through improving data accuracy, strengthening collaboration, and ensuring adequate resources to sustainably reduce poverty rates in West Pasaman Regency.